Dog man : for whom the ball rolls - Pilkey, Dav.; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2019)
The Supa Buddies have been working hard to help Dog Man overcome his bad habits. But when his obsessions turn to fears, Dog Man finds himself the target of an all-new supervillain! Meanwhile, Petey the Cat has been released from jail and starts a new life with Li'l Petey. But when Petey's own father arrives, Petey must face his past to understand the difference between being good and doing good.
Fore-foreword: dog man: behind the refined sophistication! -- foreword: our story thus far -- 1. Rise of the planet of the cats -- 2. Behavioral modification therapy -- 3. To heck with the planet of the cats -- 4. To heck with the planet of the cats -- 5. Papa knows best -- 6. A Buncha stuff that happened -- 7. Guess who's coming to breakfast! -- 8. The old man and the seafood crackers -- 9. Burgle balls attack -- 10. Do good -- 11. The very hangry catterpillar -- 12. A farewell to arms -- 13. Commander cupcake returns -- 14. The mud and the stars -- Sarah Hatoff News Blog -- Notes -- How to Draw.
Keywords: Comic Books